Internal and External Factors Determining Foreign Policy of Iran: Prospects and Perspectives - ALIYEV, ANAR; ASHIFA, DR.KM (The journal of contemporary issues in business and government, 2021)
The present paper tried to analyse external and internal factors which effecting Iran’s foreign policy. Iran is one of the most important and effective powers of the Middle East due to its geopolitical position, natural resources, power of influence, historical and cultural background, and ideological attitude after the 1979 Revolution. The determination of the mental, psychological, physical environment and conditions in which decision-makers make their foreign policy decisions is considered as one of the important facts in terms of foreign policy analysis. It is known that besides external factors, internal factors are also effective in determining foreign policy decisions. However, realist movements made a basic distinction between domestic and foreign policy and did not address the role of internal factors in influencing foreign policy. The realist movement argues that external factors, as well as internal factors, are also formed within the sovereign boundaries of states, but the main point of separation is that external factors focus on activities outside the sovereign borders of the state. They emphasize that states are accepted as the main actors in the international system and foreign policy is determined by states as a whole